If a and b are the roots of the quadratic equation 2r + 6x -7 = 0, form the equation with the following causes.
[tex] \frac{1}{2 \alpha + 1} \frac{1}{2 \ \beta + 1 } [/tex]

Respuesta :

Answer:

Step-by-step explanation:

Assuming the given equation is actually [tex]2x^2+6x-7=0[/tex].

Then [tex]\alpha +\beta=-\frac{6}{2} =-3,and,\alpha \beta=-\frac{7}{2}[/tex]

The sum of roots of the new equation is [tex]\frac{1}{2\alpha+1} +\frac{1}{2\beta +1} =\frac{2(\alpha+\beta+1)}{4\alpha \beta+2(\alpha +\beta)+1}[/tex]

[tex]\implies \frac{1}{2\alpha+1} +\frac{1}{2\beta +1} =\frac{2(-3+1)}{4*-3.5+2(-3)+1} =\frac{4}{19}[/tex]

The product of the roots of the new equation is [tex]\frac{1}{2\alpha +1}*\frac{1}{2\beta+1}=\frac{1}{4\alpha \beta+2(\alpha+\beta)+1}[/tex]

[tex]\implies \frac{1}{2\alpha +1}*\frac{1}{2\beta+1}=\frac{1}{4*-3.5+2(-3)+1} =-\frac{1}{19}[/tex]

The new equation is given by:

[tex]x^2-(sum\:of\:roots)x+product\:of\:roots=0[/tex]

[tex]x^2-\frac{4}{19} x-\frac{1}{19} =0[/tex]

[tex]19x^2-x-1=0[/tex]